A traffic engineering system for multilayer networks based on the GMPLS paradigm. - Iovanna, P.
This article discusses a novel approach for realizing traffic engineering in the framework of new-generation multilayer networks based on the GMPLS paradigm. In particular, the proposed traffic engineering system is able to dynamically react to traffic changes while at the same time fulfilling QoS requirements for different classes of service. The proposed solution consists of a hybrid routing approach, based on both offline and online methods, and a novel bandwidth management system that handles priority, preemption mechanisms, and traffic rerouting in order to concurrently accommodate the largest amount of traffic and fulfill QoS requirements. The bandwidth resources of the network are effectively exploited by means of "elastic" utilization of the bandwidth. The main building blocks and operations of the system are reported, and the major advantages are discussed.
Keywords: GMPLS; QoS requirements; SDH/SONET.; WDM; Bandwidth management; Classes of service; Elastic bandwidth utilization; Hybrid routing; New-generation multilayer networks; Offline methods; Online methods; Preemption mechanisms; Priority; Traffic engineering; Traffic rerouting